Diagnostic performance of US for suspected appendicitis: Does multi-categorical reporting provide better estimates of disease in adults, and what factors are associated with false or indeterminate results?. Issue 144 (November 2021) - Froc, Alexander; Crocker, Candice; Abdolell, Mohamed; Costa, Andreu F.
Highlights: Females and absence of tenderness are associated with a false/indeterminate US. Age, scan time, and radiologist subspecialty are not associated with US result. Multi-categorical reporting of US provides more granular estimates of appendicitis. Abstract: Purpose: To identify factors associated with false or indeterminate US result for suspected appendicitis, and assess whether multi-categorical reporting of US yields more precise estimates regarding the probability of appendicitis. Methods: 562 US examinations for suspected appendicitis between May 2013-April 2015 were categorized as true (77/562 true positives or true negatives) or false/indeterminate (485/562 false negatives, false positives or indeterminates) based on results from a prior study. Of 541 examinations with images available retrospectively, a category of A–E was assigned as follows: non-visualized appendix with secondary findings (A) absent or (B) present; appendix visualized and considered (C) negative, (D) equivocal, or (E) positive for appendicitis. The following factors were recorded: age; sex; scan time (daytime vs. off-hours); resident/fellow involvement; abdominal subspecialty radiologist; radiologist experience (>5 years or not); and tenderness on interrogation. Associations between factors and US result were assessed (t-tests, Fisher's exact test and multivariate logistic regression). Results: The true group had proportionally more males (18/77 (23.4%) vs. 66/485 (13.6%), p = 0.04) and patients with sonographic tenderness (43/77 (55.8%) vs. 132/353 (27.3%), p < 0.0001). There was no significant difference or association with other factors. On multivariate logistic regression, false/indeterminate results were 1.9 times (95% CIs 1.0–3.5) more likely among females and 3.8 times more likely in the absence of tenderness (95% CIs 2.3–6.4). The proportion of patients with appendicitis in categories A-E was 34/410 (8.3%), 24/44 (54.5%), 0/18 (0%), 0/3 (0%) and 61/66 (92.4%), respectively. Conclusions: Females and absence of tenderness were associated with a false/indeterminate US. Categorical reporting provides more granular estimates of the post-test probability of appendicitis.